ВИКЛАДАННЯ ІНОЗЕМНОЇ МОВИ З ВИКОРИСТАННЯМ ІНТЕРАКТИВНИХ МЕТОДІВ НАВЧАННЯ В ЗАКЛАДАХ ОСВІТИ І-ІІ РІВНЯ АКРЕДИТАЦІЇ (Педагогіка вищої та середньої школи, 2008)
In article to be considered effectiveness of using interactive methods of studying in the process of learnin foreign languages in higher educational of 1-11 degrees of accreditation.